Response of Broiler Chicks to Xylanase Supplementation of Corn/Rye Containing Diets Varying in Metabolizable Energy - El-Wafa, S. Abou; Shalash, S.M.; Selim , N.A.; Abdel-Khalek, A.M.; Radwan, A.M.; Abdel-Salam, A.F. (International Journal of Poultry Science, 2013)
The contribution of enzyme (xylanase) supplementation (ES) to improving performance of broiler chicks fed decreased ME diets based on corn/ rye was investigated in the current study. Three hundred-sixty-one day old Arbor Acres chicks were randomly allocated in a 2x3x2 factorial design in twelve experimental groups, three replicates per group and ten birds per replicate. Experimental diets were based on two Cereal Sources (CS); corn alone or rye contributing to 10% of the whole diets that differed on dietary ME levels [positive control according to strain recommendations, negative control 1; 50 kcal/kg ME less than recommended and negative control 2; 100 kcal/kg ME less than recommended] at supplemental xylanase doses 0 or 16,000 U/kg diet. Feeding rye to broilers had no negative effect on total Feed Conversion Ratio (FCR) which could compensate for the significant decrease in accumulative live weight gain (BWG) compared to total corn grain feeding. Data on the effect of dietary ME level reveal a significant decrease in total BWG associated with a corresponding increase in total FI and a worsening in FCR as the dietary ME decreased. Inclusion xylanase significantly improved FCR without affecting total BWG and decreasing both abdominal fat content and liver weight. Dressing percentage was not affected by main factors investigated. Interactions studied show no significant effects on growth and most noticeable significant interactions are those for the total FCR between CSxME and CSxES. Treatments have a limited effect on the absence/presence of some pathogenic bacteria. So far it can be include rye in broiler chick diets at the rate of 10% with xylanase supplementation providing that the dietary ME level be kept within the recommendations. While enzyme supplementation is recommended in case of decreasing dietary ME level.